2016
DOI: 10.1111/apps.12073
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Psychology of Entrepreneurship: A Review of the Psychological Literature and an Introduction

Abstract: This article provides a narrative review of psychology of entrepreneurship research published in leading psychology journals, based on which we develop an organising framework for future psychological contributions to this field. Furthermore, we introduce the manuscripts collected in this special issue. Our review identified five research areas, broadly corresponding with basic psychological domains, namely personal differences; careers; health and well-being; cognition and behaviour; and leadership; as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(136 citation statements)
references
References 195 publications
2
120
0
5
Order By: Relevance
“…Third, our study contributes to the entrepreneurship literature on effectuation from a psychological perspective (Gorgievski & Stephan, ). Specifically, our study joins the recent psychological micro‐foundational movements on organisation and management studies (Liu et al, ) by suggesting resilience as a micro‐foundation for effectuation theory in the context of entrepreneurs dealing with risk.…”
Section: Discussionmentioning
confidence: 80%
“…Third, our study contributes to the entrepreneurship literature on effectuation from a psychological perspective (Gorgievski & Stephan, ). Specifically, our study joins the recent psychological micro‐foundational movements on organisation and management studies (Liu et al, ) by suggesting resilience as a micro‐foundation for effectuation theory in the context of entrepreneurs dealing with risk.…”
Section: Discussionmentioning
confidence: 80%
“…Positive affect that strengthens persistence was found to mitigate the negative impact of stress on the physical health of the entrepreneurs. A positive relationship between MWB and firm performance has been noted (Gorgievski et al 2010;Gorgievski and Stephan 2016).…”
Section: Entrepreneur Mental Health and Well-beingmentioning
confidence: 93%
“…The individual characteristics that make an entrepreneur have been a matter of significant interest in both research (Shane 2003;Parker 2009;Gorgievski and Stephan 2016) and popular press (The Economist 2012). Studies have shown that individuals who engage in entrepreneurship score high in an array of characteristics such as energy level, persistence (Neider 1987), selfefficacy, openness to new experience, need for achievement, entrepreneurial orientation (characterized by autonomy, innovativeness, risk-taking, proactivity, and competitive aggressiveness) (Frese and Gielnik 2014), and psychological resilience (Markman and Baron 2003).…”
Section: Introductionmentioning
confidence: 99%